Abietanes from Plectranthus grandidentatus and P-hereroensis against methicillin- and vancomycin-resistant bacteria - Gaspar-Marques, C (2015)
The antimicrobial activity of 10 natural abietanes isolated from Plectranthus grandidentatus and P. hereroensis acetonic extract was evaluated against methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus faecalis (VRE). The results revealed that the most active diterpenes were coleon U (1), 7 alpha-acetoxy-6 beta-hydroxyroyleanone (2) and horminone (3). Minimum inhibitory concentration (MIC) values ranging 0.98-15.63 mu g/ml were obtained for MRSA clinical strains, and MIC values of 15.63 and 31.25 mu g/ml were obtained for VRE clinical strains. Some structure-activity relationships are emphasized. (c) 2005 Elsevier GmbH. All rights reserved.